Modifikasi Produksi dan Biaya Bahan Bakar Minyak pada Kapal Ciremai - Sijabat, Eduard Alfian Syamsa; Fransisca, Ribka; Suparman, Asep; Setiawan, Edhie Budi; Thamrin, Muhammad; Ichwan, Gema Akbar (Institut Transportasi dan Logistik Trisakti, 2024)
Some of the main research problems are the lack of fuel efficiency use, difficulties in loading and unloading process, the refueling process tardiness and the ships route’s delay of the determined and planned routes that could affect the Ciremai Ship’s On Time Performance (OTP). The research aims to determine and analyze the effect of production and fuel oil cost modifications based on the income of Ciremai Ship and its implications for its financial performance after “Three in One” modification. This research used Descriptive statistical analysis method and hypothesis testing using SmartPLS-3. The research sample was taken from the entire routes of Ciremai Ship over the last four years of 48 months. The secondary research data was taken from the financial reports related to production modifications, fuel oil costs, the income and financial performance of the ship. Research findings show that the production modifications have a direct influence on financial performance while fuel costs and income do not have a direct influence on it. The production modifications do not have a direct effect on income instead fuel costs have a direct effect on income and production modifications do not have an indirect effect on financial performance through income.